Gender disparity in access to information and extension services in dairy farming - Bhuyan, Maneesha; Ponnusamy, Kuppusamy (Journal of Extension Education, 2018)
A study on the role of men and women in accessing different communication sources and extension services in dairy farming was undertaken during 2016-17 in Haryana, India with 120 randomly selected women farmers. Personal interview and PRA (Participatory Rural Appraisal) methods were used for data collection and analyzed using frequency and percentage. Majority of males had land ownership, livestock and credit. Majority of the women respondents had occasional contact with veterinary surgeons & ICAR-National Dairy Research Institute and animal feed dealers. However in case of informal sources, majority of the males had contact with relatives/ friends. Women’s role is highly reflected in fodder collection, feed preparation, cleaning of animal shed, milking and taking care of animals. This gender disparity brings urgent need to sensitize the dairy farmers/farm women and enable them to have equal access of resources, input and opportunities through appropriately designed extension models for ultimate empowerment of farm women and the progress of the country.